Soot loading estimation model and passive regeneration characteristics of DPF system for heavy-duty engine. (5th May 2016) - Bai, Shuzhan; Tang, Jiao; Wang, Guihua; Li, Guoxiang
Highlights: A new soot model was established to calculate the soot accumulation in DPF. The temperature field in the DPF was measured in DPF. The new soot model includes transient soot emission and chemical reaction module. Temperature and NO2 concentration are key points for regeneration time interval. Abstract: Although the pressure differential sensor across the DPF could estimate the amount of soot in the DPF, the accuracy of the soot estimation deteriorates seriously at lower exhaust volumetric flow. In order to compensate for this defect, a new soot loading model was established to calculate the soot accumulation in the DPF for improving the accuracy of active regeneration trigger time, and passive regeneration is researched based on this model. Testing validations were taken based on WHTC test cycle. The results show that the average error between calculated and measured soot loading is about 3.4% during the soot loading process. With the increasing tailpipe temperature and NO2 concentration, passive regeneration is accelerated and active regeneration interval is prolonged. When temperature after turbo reaches 283 °C with 289 ppm NO2 concentration, soot loading maintains around 1.27 g/L. At this balance point, pure passive regeneration can be fulfilled.